The prospects of people with disabilities (PWDs) participation in entrepreneurship: the perspective of university students with physical and sensory disabilities - Norafandi, Muhammad Nur Aizuddin; Mohamad Diah, Nurazzura (Zes Rokman Resources, 2017)
The subject of disability has risen to be a topic of importance for these few decades. Various agencies and world bodies have gone into looking into this issue with keenness. One of the subjects taken into consideration within disability is disability entrepreneurship. The idea of disability entrepreneurship arises due to the fact that employability of persons with disabilities is low. More often than not, when they are employed, they are given a salary that is much lower than what others, who work the same jobs, receive. With this, the main objective of this study is to describe the belief of persons with disabilities participation in entrepreneurship. The study employed qualitative design. Ten persons with disabilities, mainly youths aged between 19-25 years were recruited via purposive sampling. Data was collected using in-depth interviews, transcribed and analyzed using qualitative technique. This study reveals that entrepreneurship is a pivotal means to empower PWDs. Participation in entrepreneurship has increased their self-power and self-reliance. They are also able to lead a life of dignity in accordance with their values. In addition, participation in entrepreneurship for PWDs is not merely a source of income, but at the same time it helps them to satisfy their psychological and social needs. Psychologically, participation in entrepreneurship strengthened their self-esteem, independence and reduces the feeling that disabilities are manifestations of their deficiency. Also, entrepreneurship enables them to be socially inclusive and to contribute to the development of the society through charity and donations. In these ways, they may contribute to the well-being of the community of which they are a part of despite their disabilities. Serious efforts should be made to develop awareness among Malaysians on the importance of PWDs participation in entrepreneurship. PWDs are an integral part of the Malaysian society and as such it is the responsibility of the society to enable them to lead a dignified life and contribute effectively to nation-building. This study also expects to add to the scarce literature on disability issues, within the Malaysian context, specifically in business and entrepreneurship.